Experts and Epidemics - Klaus Gründler; Niklas Potrafke (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Do experts adjust their policy recommendations when the facts change? We conduct a large-scale randomized experiment among 1,224 economic experts across 109 countries that includes two treatments. The first treatment is the geographic and temporal variation in the initial spread of Covid-19 during March 2020, which we use as a natural experiment. The second is a randomly assigned information treatment that informs experts about the past macroeconomic performance of their country. We find that greater exposure to Covid-19 decreases the probability to recommend contractionary fiscal policies. A better macroeconomic performance increases the probability to implement contractionary policies and reduces the exposure effect to Covid-19. While our results show that experts adjust their policy recommendations to changing environments, sentiment analyses of open-ended questions asked after the treatment suggest that these adjustments are caused by Bayesian information updating and not by a change in preferences.
Keywords: A11; E62; H60; H63; 330; epidemics; Covid-19; health; experts; fiscal preferences; randomized experiment